Partnership coordination for optimized COVID-19 vaccination: a case study of Benue and Niger states - Isiaka, Saheed Dipo; Samuel, Olugbemisola Wuraola; Jimoh, Akolade Uthman; Atobatele, Sunday; Sampson, Sidney; Daniel, Victor; David, Joshua Cinwonsoko; Odira Okoye, Irene; Adegoke, Zubair (Frontiers in Public Health, 2024)
Background Developing countries have partnered with non-governmental and development organizations to ensure universal health coverage and promote equity in accessing health services. This study was motivated by the timely and relevant collaborative partnership among the National Primary Health Care Development Agency (NPHCDA), Sydani Consulting, and other implementing partners at the sub-national level. There is also no evidence of a study on partnership coordination vis-à-vis COVID-19 vaccine optimization. Objective This study seeks to examine the influence of partnership coordination in Benue and Niger states for optimized COVID-19 vaccination. Methods This study adopted a qualitative approach to obtain data from purposively selected participants from Benue and Niger states. Fifty-sox In-depth and Key informant interviews were conducted. The recorded discussions were transcribed and coded (inductively and deductively) using Dedoose software (v9.0). Four themes and seven sub-themes were generated from the participants' responses. Results Findings from our study revealed that partners played significant roles in providing support to Benue and Niger states toward the optimization of COVID-19 vaccination in the two states. The provided support alleviated several challenges experienced by the states before the advent of partners in the two states. Partners' roles were assessed using the WHO Health Building Blocks Framework. Conclusion Our study concludes and finds it plausible that partner collaboration can effectively improve health outcomes for the populace, especially in resource-low settings.